Предмет: Алгебра,
автор: Тотсамый123
Преобразуйте выражения в многочлен стандартного вида:
a) (2a-3)^2
б) (3а-4в)*(3а+4в)
в) (-2)*(х:2+2х+4)
Ответы
Автор ответа:
0
a) (2a-3)^2=4a²-12a+9
б) (3а-4в)*(3а+4в)=9a²-16b²
в) (-2)*(х:2+2х+4)=-2x²-
б) (3а-4в)*(3а+4в)=9a²-16b²
в) (-2)*(х:2+2х+4)=-2x²-
Похожие вопросы
Предмет: Информатика,
автор: nastyakorolevskaya99
Предмет: Математика,
автор: aksenovaksenia56
Предмет: Французский язык,
автор: nazerkekazbekova421
Предмет: История,
автор: Annikaaa
Предмет: Алгебра,
автор: yana040101